1989
DOI: 10.1136/vr.125.18.450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of general anaesthesia on static respiratory compliance in dogs

Abstract: The effect of anaesthesia on total, pulmonary and chest wall static respiratory compliance was investigated in healthy spontaneously breathing dogs undergoing orthopaedic surgery. Total compliance fell by 26 per cent from the baseline measurement within 25 minutes of the first measurement (P less than 0.01), while pulmonary and chest wall compliances fell by 34 per cent and 40 per cent, respectively (P less than 0.01). Pulmonary compliance ceased to fall after 50 minutes, but chest wall compliance was still de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using the same method as in the present study, Gold and others (1972) found a lower CL in anaesthetised, paralysed and artificially ventilated dogs, but they could increase compliance by intermittent manual inflation. CL and CW are reduced markedly during general anaesthesia and this fall could be reversed by full lung inflation (Mead andCollier 1959, Corcoran andAbercromby 1989). In a series of trained unanaesthetised experimental dogs, CL and CW were greater than in the present study, but CT was the same when corrected for bodyweight (Gillespie and Hyatt 1974).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Using the same method as in the present study, Gold and others (1972) found a lower CL in anaesthetised, paralysed and artificially ventilated dogs, but they could increase compliance by intermittent manual inflation. CL and CW are reduced markedly during general anaesthesia and this fall could be reversed by full lung inflation (Mead andCollier 1959, Corcoran andAbercromby 1989). In a series of trained unanaesthetised experimental dogs, CL and CW were greater than in the present study, but CT was the same when corrected for bodyweight (Gillespie and Hyatt 1974).…”
Section: Discussionmentioning
confidence: 51%
“…At least 15 minutes elapsed between induction of anaesthesia and starting compliance measurements. The anaesthetic protocol and procedure for measuring compliance have been reported previously (Corcoran and Abercromby 1989 anaesthesia was maintained with 0.5 to 2 per cent halothane (RMB Animal Health), 70 per cent nitrous oxide and 30 per cent oxygen using a semi-closed rebreathing system.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement using the load cell proved to be a reliable method of determining tension in the girth because the values recorded were not influenced by torsional forces applied in other directions across the device. Although resting thoracic mechanical properties of dogs, cattle and horses have been described, (Corcoran and Abercromby 1989;Koterba et al 1994;Desmecht et al 1997) and respiratory mechanics of horses during strenuous exercise (Derksen et al 1986;Art et al 1990;Slocombe et al 1991Slocombe et al , 1992 we were unable to fiid any descriptions of similar studies either in animal or human athletes where the influence of thoracic constriction by garments or tack has been studied. However, abdominal constriction in patients with chronic obstructive airway disease was found to reduce dyspnoea at rest but negatively affected endurance in patients performing bicycle exercise tests to fatigue @odd et al 1985).…”
Section: Discussionmentioning
confidence: 88%
“…In all cases, full histories were taken and (Rebar and DeNicola 1988). Material for cytology was centrifuged (Cytospin; Shandon), stained with haematoxylin and eosin, Papanicolaou and Leishman's stains and examined microscopical-Respiratory compliance was measured as the slope of the static pressure-volume curve of the respiratory system as described by Corcoran and Abercromby (1989). Pressure-volume curves for the total respiratory system, lung tissue and chest wall were measured from which total, pulmonary and chest wall compliance were calculated.…”
Section: Methodsmentioning
confidence: 99%